The impact of non dental glass fiber addition against tensile strength pre-polymerized fiber reinforced composite - eko Hadianto; Nurfika Sofiana; Moh Yusuf (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Composite resin is one of the most used materials in dentistry because of the simplicity and high aesthetic value. One of the varieties of composite resin is prepolymerized composite resin. Some research show that prepolymerized composite resin has relatively low mechanical strength. Therefore fiber needs to be added in prepolymerized composite resin. The aim of this research is to find out the effect of adding non dental glass fiber into tensile strength fiber reinforced composite. Method: This research used true experimental method with post test only control group design, there are two groups, the first one is prepolymerized composite resin with additional non dental glass fiber. The data has been tested with parametric independent T-test. Result: The result showed the average flexural strength of prepolymerized composite resin without additional non dental glass fiber was 10.6625 Mpa, while the prepolymerized composite resin + non dental glass fiber was also 18.2263 Mpa. Independent T-test showed the p value = 0.000 Conclusion: The conclusion of this research is that prepolymerized resin + non dental glass fiber has higher tensile strength than composite resin without additional non dental glass fiber, thus it can be used as alternative choice applied in dentistry.